(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: abundant evidence exists worldwide with regards to how religiosity and/or spirituality plays a role in influencing people with Type 2 diabetes manage their daily self-care activities. Indonesia is the most populous Muslim country in the world and research suggeststhat Indonesia has among the highest incidence of diabetes in the world. However, paucity of evidences was found about the relationship of religiosity and/or spirituality to the self- care of diabetes. Methods: The objective of this structuredreview is to identify, appraise and synthesise the best available evidence worldwide, including Indonesia, related to how people with diabetes perceives the role of religion and/or spirituality in managing daily self-care. CINAHL, Ovid MEDLINE and Garuda, an Indonesian search portal were accessed to find evidence regarding self-care, religion and diabetes using the keywords ‘religion’, ‘religiosity’, ‘spirituality’, ‘selfcare’, ‘self-management’, ‘self-efficacy’, ‘diabetes’. A critical appraisal using an adapted CASP tool was utilized. Results: The first attempt collected 51,722 articles from CINAHL, 11,346 from OvidMEDLINE, 62 from ISJD, 4 from Google Cendikia and nothing from Garuda. Second attempt was done with the inclusion of ‘linked full text’, ‘references available’, ‘abstract available’, ‘1970-2012’, age range of ’19-65’ and revealed a total of 298 articles. Third attempt was done using several inclusion criteria, such as: self-management in chronic illness, quality of life in chronic illness, coping with diabetes, structured education in diabetes, and health behaviour determinants. Criteria exclusion was applied, such as: mental health, psychosis, nutrition intervention, chronic renal diseases, nurse’s coping, and dying patients. Finally, thirtyone studies were retrieved to be analysed. Several themes emerged from the evidence these included: relationship with God or the transcendent, religion or spirituality as coping methods; religious practices; and, social support. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.185-193